2023
DOI: 10.3390/languages8010033
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Tense and Aspect across Languages

Abstract: Variation across languages has always fascinated linguists, but in the past, cross-linguistic variation has mostly been investigated in form-related subdisciplines (phonetics/phonology, morphology, syntax) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In Table 2, we only listed the tuples that appear more than once, removing 15 contexts. In line with Le Bruyn et al (2022b), we hypothesized that this restriction was likely to discard tuples exhibiting translation-induced rather than grammatical variation. Manual inspection of the individual contexts suggested that this hypothesis was on the right track and given that we target grammatical variation, we proceeded with the removal of the contexts corresponding to these tuples.…”
Section: Distributional Patterns Of Perfect Formsmentioning
confidence: 96%
See 1 more Smart Citation
“…In Table 2, we only listed the tuples that appear more than once, removing 15 contexts. In line with Le Bruyn et al (2022b), we hypothesized that this restriction was likely to discard tuples exhibiting translation-induced rather than grammatical variation. Manual inspection of the individual contexts suggested that this hypothesis was on the right track and given that we target grammatical variation, we proceeded with the removal of the contexts corresponding to these tuples.…”
Section: Distributional Patterns Of Perfect Formsmentioning
confidence: 96%
“…We furthermore argue that the domain of the PERFECT scale can be narrowed down further to the perfective past domain. To make both points, we follow Le Bruyn et al (2022b) in constructing a secondary dataset based on all contexts in Chapter 1 of L'Étranger in which the languages included in our main corpus use finite indicative tense forms.…”
Section: The Perfect Scale: Robustness and Domainmentioning
confidence: 99%